Penerapan E-Government Melalui Program Dottorotta Di Kota Makassar - Andi Armayudi Syam; M. Adnan Nur; Agus Rahmat; Nurdin Khalid Sadewa (Prosiding SISFOTEK, 2023)
The aim of the research is to look at Regional Government Innovation in Health Services through the Home Care Program(Dottorotta) at the Tamangapa Community Health Center, Makassar City. The amount of information in this research was 5(five) people. This research uses qualitative research. The theory used in this research is Rogers' theory based on RelativeAdvantages, Conformity, and Complexity. The research results show that (a) Relative Advantage, from the results of innovation.Community home care is easier to access health services without having to go to the hospital even outside working hoursbecause the service is 24 hours. (b) Compatibility, providing home care services in accordance with appropriate invitationregulations. Actions for checking home care services are running according to existing norms. (c) The complexity of home careinnovation, namely 24 hour service when people need service in certain situations such as in the middle of the night but fromhome care providers who are not ready, this will certainly make home care innovation difficult. And public understanding ofhealth service programs is still lacking. (d) The facilities and infrastructure at the Tamangapa Community Health Center areadequate so that the implementation of the Home Care (Dottorotta) innovation can run smoothly and seamlessly.